PENGARUH SUBSTITUSI BUAH SUKUN (ARTOCARPUS COMMUNIS) DAN KACANG HIJAU (VIGNA RADIATA) TERHADAP DAYA TERIMA DAN KANDUNGAN PROTEIN FLAKES - Alzha Adila Harisina; Annis Catur Adi; Farapti Farapti (Universitas Airlangga, 2016)
Breadfruit is staple food of carbohydrate source alternative, while the mung beans is source of vegetable protein that potential to be processed as fl akes for supplementary feeding of schoolchild. This research aims to determine the effect of breadfruit and mung beans substitution toward the acceptance and protein content, as well as determine the best formula to produce a quality fl akes. Type of research is true experimental design with completely randomized design with 3 times replicating. Untrained panelists were used 34 2nd elementary school students. Product acceptance was tested using statistical analysis Chi square (α ≤ 0.005). The result of product acceptance test shown the most preferred panelist is fl akes F1 (breadfruit 50g, mung beans 50 g, and tapioca fl our 50 g) which have mean value of the highest rank in the aroma characteristic (87.00), texture (95.00) and taste (89.50), while the color values meanrank (77.5) under the color of the basic formula (83.5). F1 has 9.8 g protein content per serving. Statistical analysis of acceptance differences using chi square test on the assessment of the color, aroma, texture and fl avor showed signifi cant differences (α ≤ 0.05) on each characteristic between F0 to F2, F0 to F3, F1 with F2 and F1 to F3, whereas there wasno signifi cant difference (α ≥ 0.05) for the acceptance of color, aroma, texture and fl avor fl akes F0 to F1 and F2 to F3. The best composition, acceptability, and nutritional value was found in F1 (breadfruit 50 g, mung beans 50 g, and tapioca fl our 50 g) and can be used as alternative of supplementary feeding for school students.Keywords: Breadfruit, acceptance, fl akes, mung beans, protein